Russia's foreign policy: key regions and issues - Orttung, Robert; Perovic, Jeronim; Pleines, Heiko; Schröder, Hans-Henning; Forschungsstelle Osteuropa an der Universität Bremen (DEU, 2015)
Contents: Part I: Russia's relations with key regions of the world. Russia and the West - Andrei Zagorski: Moscow seeks to renegotiate relations with the West (7-10); Sabine Fischer: The EU and Russia: stumbling from summit to summit (15-17); Andrew Monaghan: Prospects for developing NATO - Russia relations (19-21). Russia and Central Asia - Aleksei Malashenko: Russia and Turkmenistan (25-28); Alisher Ilkhamov: Russia lures Uzbekistan as its strategic satellite in Central Asia (31-34); Martha Brill Olcott: The Kazakh-Russian relationship (37-40). Russia and Asia - Gilbert Rozman: Russia's resurgence in Northeast Asia: views from the region (45-48); Oksana Antonenko: Russia, Central Asia and the Shanghai Co-operation Organization (49-53). Nuclear proliferation - Adam N. Stulberg: Russia's nonproliferation tightrope (65-68). Maritime border conflicts - Vlad M. Kaczynski: US-Russian Bering Sea marine border dispute: conflict over strategic assets, fisheries and energy resources (75-78); Vlad M. Kaczynski: The Kuril Islands dispute between Russia and Japan: perspectives of three ocean powers (79-82); Geir Honneland: Norway and Russia in the Barents Sea - cooperation and conflict in fisheries management (82-85). Part II: pressing issues: WTO accession - Peter Rutland: Russia and the WTO: one step forward, one step back (89-91); Natalya Volchkova: Russia and the WTO: a Russian view (92-95); Documentation: World Trade Organization: principal objectives and functions, accession procedure (95); Documentation: Economic effects of Russian WTO accession (96-103).